Competências esperadas de um engenheiro e o projeto pedagógico do curso de Engenharia Mecânica da UFSCar: uma análise comparativa - Lima, Filipe Cesar Silva (Universidade Federal de São Carlos, 2022)
It is expected of all the people that graduates on a university that they obtain competences, knowledge and skills throughout their course to be able to work in their area of expertise. The curricular guidelines of Engineering are the ones that guide the courses on the construction of the expected profile in their Pedagogical Projects and curricula. Thus, in the present work, a bibliographic research was carried out in order to build a database for analysis. This database was composed of 10 articles that had as results and conclusions what are the most important skills for an engineer to have from the point of view of professionals in the area, teachers, students and graduates of Engineering courses. After that, a comparative analysis was made with the Pedagogical Project of the Mechanical Engineering course at UFSCar in order to understand if what the publications indicate as the main competences, are contemplated in the objectives and curriculum of the UFSCar course. Finally, it is concluded that the Pedagogical Project includes 93% of the competences, knowledge and skills listed, but it was not possible to analyze the practical application of the Pedagogical Project. It was noticed that there are also few studies in this area focused on Mechanical Engineering itself, which made it more difficult to compare the results.
Skills expected from an engineer and the pedagogical project of the Mechanical Engineering course at UFSCar: a comparative analysis
Keywords: Conhecimentos; Diretrizes curriculares; Engenharia; Habilidades; ENGENHARIAS::ENGENHARIA MECANICA